1992
DOI: 10.1007/bf00966831
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C in rat brain myelin

Abstract: It has been suggested that phosphorylation of myelin basic protein (MBP) in CNS is catalyzed by protein kinase C (PKC). In order to demonstrate that PKC in the myelin phosphorylates MBP, PKC was partially purified from rat CNS myelin by solubilization with Triton X-100 followed by a DEAE-cellulose column. MBP and histone III-S were phosphorylated in the presence of Ca2+ and phospholipid by rat myelin PKC. High voltage electrophoresis revealed that the phosphoamino acids in MBP by this kinase was serine residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…While the precise time frame is region-specific (Foran and Peterson, 1992), myelin formation generally begins in the first postnatal week and peaks between the second to the fourth postnatal weeks of life (Norton and Poduslo, 1973;Monge et al, 1986;Bjartmar et al, 1994). The expression of PKC also follows this temporal profile, as demonstrated by increased binding of radiolabeled PKC ligands to, or increase of PKC enzyme activity in, the rodent corpus callosum (Shoyab et al, 1976;Girard et al, 1985;Hashimoto et al, 1988;Yoshimura et al, 1992). With respect to MMP expression, Figure 6 demonstrates that MMP-9 expression in the murine corpus callosum is low at postnatal day 7, and this then increases steadily from postnatal days 14 to 28, a temporal pattern that coincides with developmental myelination.…”
Section: Correlation Of Mmp-9 Levels and Myelination In Vivomentioning
confidence: 92%
“…While the precise time frame is region-specific (Foran and Peterson, 1992), myelin formation generally begins in the first postnatal week and peaks between the second to the fourth postnatal weeks of life (Norton and Poduslo, 1973;Monge et al, 1986;Bjartmar et al, 1994). The expression of PKC also follows this temporal profile, as demonstrated by increased binding of radiolabeled PKC ligands to, or increase of PKC enzyme activity in, the rodent corpus callosum (Shoyab et al, 1976;Girard et al, 1985;Hashimoto et al, 1988;Yoshimura et al, 1992). With respect to MMP expression, Figure 6 demonstrates that MMP-9 expression in the murine corpus callosum is low at postnatal day 7, and this then increases steadily from postnatal days 14 to 28, a temporal pattern that coincides with developmental myelination.…”
Section: Correlation Of Mmp-9 Levels and Myelination In Vivomentioning
confidence: 92%
“…PKC-y is reported to be expressed in brain and spinal cord but not in other tissues (Shearman et al, 1987). PKC purified from rat brain myelin contains at least PKC-a and PKC-P (Yoshimura et al, 1992). The Ca++-independent isozymes PKC-8, -E, -5, -q -fi and -8 have been identified in brain, heart, muscle, liver, kidney, lung, skin and hematopoietic cells (On0 et a]., 1988Schaap et al, 1989;Osada et al, 1990;Bacher et al, 1991;Koide et al, 1992;Nakanishi and Exton, 1992;Nakanishi et al, 1993;Baier et al, 1993;Bogoyevitch et al, 1993;Wang et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, PKC enzyme levels increase gradually at birth and then peak between 14 and 28 days postnatally in the rodent brain (Shoyab et aI., 1976;Hashimoto et aI., 1988), a period which correlates with in vivo myelination (Norton and Poduslo, 1973;Monge et aI., 1986;Bjartmar et aI., 1994). Furthermore, Yoshimura et al (1992) demonstrated that there is high PKC activity in rat CNS myelin and that the PKC levels from postnatal 14 to 42 days parallel the deposition of myelin proteins. Thirdly, several myelin proteins are good substrates for PKC-mediated phosphorylation and these include myelin basic protein (MBP) (Turner et aI., 1982;Vartanian et aI., 1986), 2' ,3'-cyclic nucleotide phosphohydrolase (Vartanian et aI., 1992) and myelin associated glycoprotein (Kirchoff et aI., 1993;Yim et aI., 1995).…”
Section: Evidence That Protein Kinase C Regulates Oligodendroglial Prmentioning
confidence: 95%